The Effect of Lecture Timing on Learning Outcomes in Multivariable Calculus Using One-Way ANOVA - Afifah, Ngizatul; Angrenani, Arin Berliana; Mutammam, Muhamad Badrul; Fazira, Shima Kunaza; Firmansyah, Frenza Fairuz; Salim, Abdurrahman (Department of Mathematics Education , University of Jember, 2024)
This study aims to investigate the effect of lecture timing on learning outcomes in Multivariable Calculus using One-Way ANOVA. The type of research is quantitative. The subjects of this study are students of the Mathematics Education program at Jember University from class of 2023, for the Academic Year 2024-2025, enrolled in the regular Multivariable Calculus course. The samples were purposively selected: Class A (morning class) with 35 students, Class B (afternoon class) with 37 students, and Class E (evening class) with 30 students. The sample data were free of outliers, normally distributed, and homogeneous. The results show that and p-value < 0.05, indicating that at a 95% confidence level, there is at least one pair of treatments with significantly different average learning outcomes. Based on the Post Hoc test, significant differences in average learning outcomes were found between Class A and Class B, and between Class A and Class E, while betweet Class B and Class E did not show significant differences in average learning outcomes. Keywords: learning outcomes, lecture timing, One-Way ANOVA